Prevalence of Convergence Insufficiency among Elementary School Children - Letourneau, J.E.; Ducie, S. (Canadian Journal of Optometry, 2026)
In order to determine the prevalence of convergence insufficiency among children aged 5-13, a survey was carried ow in six prima.,y schools in Montreal with a total of 2,048 students of both sexes. The overall prevalence was 2.25% (CI95% =1.6-2.9) which is Less than found in most other studies. Previous prevalence estimates and the possible reasons for this discrepancy, rhe clinical significance of convergence insufficiency and the diagnostic methods are discussed.